Trade Policy and WTO Accession for Economic Development : Application to Russia and the CIS, Module 2. Openness, Growth and Poverty - Navaretti, Giorgio Barba (World Bank, Washington, DC, 2017)
This book examines the effects of trade on growth and poverty. It addresses the following questions:1) Which are the channels through which trade openness may affect the economic activities of a given country? ; 2) What are the effects of trade openness on growth? ; and 3) What are the effects of trade openness on poverty and income distribution?.